Relevance of jet magnetic field structure for blazar axionlike particle searches - Davies, J; Meyer, M; Cotter, G (American Physical Society, 2021)
Many theories beyond the Standard Model of particle physics predict the existence of axionlike particles (ALPs) that mix with photons in the presence of a magnetic field. One prominent indirect method of searching for ALPs is to look for irregularities in blazar gamma-ray spectra caused by ALP-photon mixing in astrophysical magnetic fields. This requires the modeling of magnetic fields between Earth and the blazar. So far, only very simple models for the magnetic field in the blazar jet have been used. Here, we investigate the effects of more complicated jet magnetic field configurations on these spectral irregularities by imposing a magnetic field structure model onto the jet model proposed by Potter & Cotter. We simulate gamma-ray spectra of Mrk 501 with ALPs and fit them to ALP-less spectra, scanning the ALP and B-field configuration parameter space, and show that the jet can be an important mixing region, able to probe new ALP parameter space around m a ∼ 1 – 1000